2003
DOI: 10.1017/s0003598x00092267
|View full text |Cite
|
Sign up to set email alerts
|

Social identities and the expansion of stone bead-making in Neolithic Western Asia: new evidence from Jordan

Abstract: From their research in Jordan, the authors show that the appearance of early farming and herding communities in western Asia coincided with a large expansion in stone bead production. This reflects a new social role for personal ornament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 24 publications
1
38
0
3
Order By: Relevance
“…Smoothness and brightness was even increased by manufacture through burnishing and polishing. The importance of colour in the choice of raw material for decorative items has already been observed elsewhere (e. g., Wright, Garrard 2002;Thomas 2011), and the significance of white is underlined by copies in white stone (see above). White is a fascinating, bright and shiny colour, and has a wide range of symbolic meaning in different cultures, ranging from symbols for death to symbols of the divine (Vollmar 2009).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Smoothness and brightness was even increased by manufacture through burnishing and polishing. The importance of colour in the choice of raw material for decorative items has already been observed elsewhere (e. g., Wright, Garrard 2002;Thomas 2011), and the significance of white is underlined by copies in white stone (see above). White is a fascinating, bright and shiny colour, and has a wide range of symbolic meaning in different cultures, ranging from symbols for death to symbols of the divine (Vollmar 2009).…”
Section: Discussionmentioning
confidence: 57%
“…The entire body and its decoration can be, was and is, extensively used to show and negotiate different identities, from assertive (individual) to emblematic (group), from permanent or of long duration (such as belonging to a class or kin group) to temporary (e.g., the role of shaman, participant in a ritual, etc.). Through the decoration, clothes, jewellery, makeup, but different messages can be transmitted also through entire body posture and gesture, and the endless number of combinations were used throughout prehistory up to modern times (e.g., Wright, Garrard 2002;d'Errico, Vanhaeren 2002;Taborin 2004;Yatsenko 2004;Thomas 2011 with references). Hair, for example, was used to express individual status (single, married, young mother, widow, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'pastoralist' holds many levels of meaning, and while the essence of this term relates to the 'foundation of the management of domesticated animals' (Rollefson et al 2014 and references therein), the origins of such pastoral societies and the question of their socioeconomic independence is of major importance. Following a model suggesting that their origins are in PN societies in the Mediterranean zone (Gopher 2012(Gopher : 1570(Gopher -1575, it was suggested that alongside with an economy based on animal herding, those nomad populations were also involved in additional subsistence activities (see Gopher 2012Gopher : 1570Gopher -1575 e.g., the production and exchange of beads, procurement of raw material and production of tabular scrapers and later, possibly even activities related to the metal industry (Rosen 1983;1997: 75;Quintero et al 2002;Wright & Garrard 2003;Müller-Neuhof 2006;Fujii 2011;Klimscha 2011;Abu-Azizeh 2013;Milevski 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Como ha sido demostrado en la investigación arqueológica en Europa y Eurasia, la minería y la metalurgia pueden a menudo ser mejor entendidas en el contexto de procesos económicos domésticos y comunitarios, más que en la dinámica de la economía política de élite (Knapp, 1998;Pigott, 1998;Wright y Garrard, 2003;Hanks, 2009;Hanks y Doonan, 2009). Como una forma de intensificación domésti-ca, por ejemplo, la minería puede producir tasas de retorno más altas que otros tipos de producción en ese ámbito (Shennan, 1998(Shennan, , 1999, y puede ser una eficaz estrategia de minimización de riesgo.…”
Section: Minería Y Especializaciones Artesanales De Pequeña Escalaunclassified